2015
DOI: 10.1039/c5cp03965g
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive ion transport in polyelectrolyte multilayers of poly(diallyldimethylammonium chloride) (PDADMAC) and poly(4-styrenesulfonic acid-co-maleic acid) (PSS-MA) bearing strong- and weak anionic groups

Abstract: The layer-by-layer construction of interfacial architectures displaying stimuli-responsive control of mass transport is attracting increasing interest in materials science. In this work, we describe the creation of interfacial architectures displaying pH-dependent ionic transport properties which until now have not been observed in polyelectrolyte multilayers. We describe a novel approach to create pH-controlled ion-rectifying systems employing polyelectrolyte multilayers assembled from a copolymer containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 104 publications
2
15
0
Order By: Relevance
“…In PEM formation, the deposition of polyelectrolyte will always result in neutralization of the surface charge of the outermost layer, while the overcompensation of charge becomes the driving force for subsequent deposition of the alternating polyelectrolyte. 30,44 The zeta potential reversed to À11.39 mV aer deposition of the second PAA layer. These zeta potential values were similar to results reported by Abdullayev and his coworkers, who observed a range from +15 to 32 mV for the rst layer of PEI deposition but a slightly lower range for the PAA layer of around À15 to À30 mV.…”
Section: Conrmation Of Surface Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In PEM formation, the deposition of polyelectrolyte will always result in neutralization of the surface charge of the outermost layer, while the overcompensation of charge becomes the driving force for subsequent deposition of the alternating polyelectrolyte. 30,44 The zeta potential reversed to À11.39 mV aer deposition of the second PAA layer. These zeta potential values were similar to results reported by Abdullayev and his coworkers, who observed a range from +15 to 32 mV for the rst layer of PEI deposition but a slightly lower range for the PAA layer of around À15 to À30 mV.…”
Section: Conrmation Of Surface Encapsulationmentioning
confidence: 99%
“…The deposition through electrostatic attraction can be applied with a wide variety of building blocks, allowing the incorporation of a broad range of functional units. 30 PEMs have been constructed that possess distinctive properties based on their individual polyelectrolytes, 30,31 molecular weight, 32 salt concentration, 33,34 and pH. 35 It has also been reported that the ultimate properties of PEMs are highly dependent on the outermost assembled layer.…”
Section: Introductionmentioning
confidence: 99%
“…Besides our studies, very few publications have reported on the behavior of PE in an acidic environment. In most of these studies either weak PE were chosen, which were not stable at low pH levels, or the pH was not decreased below 3.5, as is needed to truly estimate the behavior of LbL membranes during harsh acidic applications [24][25][26], whereas strong PE such as PDAMAC and PSS are constantly charged independent of pH. Menne et al [13] also showed excellent pH stability (0-14) of PE coated on ceramic UF membranes in HCl.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion of oxidation products is highly affected by the structure of the electrode surface [5,6]. Polyelectrolyte modified electrodes are of high interest [7,8].…”
Section: Introductionmentioning
confidence: 99%